2017
DOI: 10.1080/14623730.2017.1345689
|View full text |Cite
|
Sign up to set email alerts
|

Gender and school-stage associations with health-related behaviours and health-related quality of life in Spanish children

Abstract: During adolescence individuals experience a number of cognitive, physical, psychological and emotional changes which can impinge on their health and wellbeing. The aim of this study was to identify associations with five components of health-related quality of life (HRQoL) in children. Data were collected from 456 children attending one of five schools in Granada, Spain in a cross-sectional design. Females reported engaging in less physical activity than males. Females reported lower HRQoL in terms of lower ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…This may potentially explain the stronger within-group associations between in-school-hours weekly total PA and HRQoL in males within the current study, particularly when examining time in MVPA. Converse to the current study’s findings, a cross-sectional study conducted in a sample of Spanish primary school children by Knox and Muros (2017) , found that in female primary school children, PA positively predicted physical and psychological wellbeing. However for males, PA only predicted positive physical wellbeing.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…This may potentially explain the stronger within-group associations between in-school-hours weekly total PA and HRQoL in males within the current study, particularly when examining time in MVPA. Converse to the current study’s findings, a cross-sectional study conducted in a sample of Spanish primary school children by Knox and Muros (2017) , found that in female primary school children, PA positively predicted physical and psychological wellbeing. However for males, PA only predicted positive physical wellbeing.…”
Section: Discussionmentioning
confidence: 42%
“…Comparatively, in-school-hours weekly PA for females was only positively related to Total HRQoL and Physical Health Summary Scores. Previous findings by Gu et al, 2016 , Knox and Muros, 2017 demonstrated that on average, males were more active, in terms of intensity and duration of PA than females. This may potentially explain the stronger within-group associations between in-school-hours weekly total PA and HRQoL in males within the current study, particularly when examining time in MVPA.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Research conducted in different countries is of the consensus that sex differences are evident in HRQoL and its dimensions, showing that adolescent girls experience lower quality of life than boys [ 13 , 23 , 39 41 ]. Studies that have employed the Kidscreen52 have found adolescent girls to score higher than boys on school environment and lower in physical wellbeing [ 12 , 42 ].…”
Section: Introductionmentioning
confidence: 99%